Heleieth Saffioti! - Rodrigues de Almeida, Lúcio Flávio (Pontifícia Universidade Católica de São Paulo, 2011)
The author pays tribute to Heleieth Saffioti by highlighting the importance of the intellectual- militant that she was, and whose groundbreaking research transformed critical social thinking way beyond Feminism and gender studies.